Composite: The Future of Patterned Textiles - McCoy, Richard (Auckland University of Technology, 2013)
Composite is a fashion and textiles investigation that looks at creating hybrid patterned textiles that combine heat transfers and the latest technology. By using older and overlooked products – like vinyl transfers, foils and flock – with newer techniques, we can create the next generation of patterned textiles. There is design potential in utilising heat transfer’s propensity towards rigidity and corrugation, and combining it with the uniformity and predictability of digital design technology to create a new surface pattern aesthetic. These textiles are in line with the trend for composite patterns in con- temporary fashion, a movement that has strong analogies with the commercial print and publishing industries, which are also becoming increasingly hybridised. The textiles created during the course of this research were used in a range of garments and accessories and exhibited to show their potential. A multi-method action research approach was used to investigate this topic, which also extended my abilities as a textile designer and broadened my understanding of technology and technique.
Keywords: Composite; Textiles; Hybrid; Print; Transfers; Patterns